PENERAPAN E-BISNIS DALAM SISTEM INFORMASI PEMESANAN KAMAR HOTEL - MINDA MORA PURBA (Fakultas Ilmu Komputer dan Desain - Unsurya, 2016)
Hotel room booking information system is one of the implementation of the Business to Customer which includes information on booking a room available , the cost of the bill upon check -out which includes room rental charges , restoration , laundry and other costs . With the application of information systems is expected to improve service and provide information about booking a room completely and quickly to guests , especially during holidays , when weekday or during the weekend , avoid going double booking and also can provide accurate information about the number of empty rooms and can provide information if there is a change of data or costs.